Spatial Analysis of Environmental Factors Related to Dengue Hemorrhagic Fever Cases in Banyuwangi Regency, 2020-2022 - Yusva Dwi Saputra; Ririh Yudhastuti (Universitas Airlangga, 2023)
Introduction: Based on the Banyuwangi Regency Health Office, the DHF incidence rate in Banyuwangi Regency in 2022 has experienced a significant increase of 30.14 per 100,000 inhabitants, previously 5.70. DHF can be affected by environmental factors such as mosquito larvae, rainfall, and house conditions. DHF control efforts can be carried out by mapping dengue vulnerability to formulate an appropriate policy. Conversely, the spatial analysis of DHF cases in Banyuwangi is rarely found. This study aims to analyze spatial factors at DHF IR and the relationship between an environmental factor and DHF IR in Banyuwangi Regency. Methods: This study used an ecological study approach. The data used was secondary data from 2020–2022. Data were obtained from Banyuwangi Regency Health Office and Banyuwangi Regency Central Statistic Agency. Moran's I and LISA determined the spatial autocorrelation. Spatial regression was also used in this study. Results and Discussion: DHF IR Banyuwangi Regency had spatial autocorrelation (p-value=0.0010) with clustered patterns (I=0.4789). The pattern of clustering dengue cases in an area could occur because of a relationship with previous dengue cases. Spatial autocorrelation was not found between DHF IR with LFI (p-value=0.4560), rainfall (p-value=0.0610), CBTS villages (p-value=0.1870), and healthy houses (p=value=0.3680). The independent variable in this study did not have a significant relationship with DHF IR. Conclusion: The average DHF IR in Banyuwangi Regency in 2020–2022 had a grouping pattern related to district proximity. LFI, rainfall, CBTS villages, and healthy houses had no significant relationship with DHF IR.